Body size phenology in a regional bee fauna: a temporal extension of Bergmann's rule. (19th October 2016) - Osorio‐Canadas, Sergio; Arnan, Xavier; Rodrigo, Anselm; Torné‐Noguera, Anna; Molowny, Roberto; Bosch, Jordi
Abstract: Bergmann's rule originally described a positive relationship between body size and latitude in warm‐blooded animals. Larger animals, with a smaller surface/volume ratio, are better enabled to conserve heat in cooler climates (thermoregulatory hypothesis). Studies on endothermic vertebrates have provided support for Bergmann's rule, whereas studies on ectotherms have yielded conflicting results. If the thermoregulatory hypothesis is correct, negative relationships between body size and temperature should occur in temporal in addition to geographical gradients. To explore this possibility, we analysed seasonal activity patterns in a bee fauna comprising 245 species. In agreement with our hypothesis of a different relationship for large (endothermic) and small (ectothermic) species, we found that species larger than 27.81 mg (dry weight) followed Bergmann's rule, whereas species below this threshold did not. Our results represent a temporal extension of Bergmann's rule and indicate that body size and thermal physiology play an important role in structuring community phenology.